2019
DOI: 10.1590/0001-3765201920170831
|View full text |Cite
|
Sign up to set email alerts
|

Sambucus australis Modulates Inflammatory Response via Inhibition of Nuclear Factor Kappa B (NF-kB) in vitro

Abstract: Medicinal plants have long been used as an alternative to traditional drugs for the treatment of inflammatory conditions due to the classical side effects and restricted access of various commercially available drugs, such as steroids (GCs) and nonsteroidal anti-inflammatory drugs (NSAIDs). Sambucus australis is a Brazilian herb that is commonly used to treat inflammatory diseases; however, few studies have examined the use of this species in the treatment of inflammatory conditions. The present study aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In these, a chronic inflammatory state is the major contributing factor to their development [ 3 , 4 ]. Berries, and, among them, black chokeberry ( Aronia melanocarpa L.) are fruits immensely rich in in natural compounds, including vitamins, minerals, dietary fibers and polyphenols [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these, a chronic inflammatory state is the major contributing factor to their development [ 3 , 4 ]. Berries, and, among them, black chokeberry ( Aronia melanocarpa L.) are fruits immensely rich in in natural compounds, including vitamins, minerals, dietary fibers and polyphenols [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 ). NF-κB is responsible for producing cytokines, chemokines, and growth factors, thereby regulating the expression of genes involved in immune and inflammatory responses [ 30 ]. Our results suggest that PEITC and DIM supplementation inhibits the inflammatory molecules COX-2, IL-6, and NF-κB p65 in splenic inflammation induced by a HFCD.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that various NF-κB defects are indicated by immune dysregulation, with features of autoimmunity and inflammation[28]. NF-κB is a transcription factor that involved in the expression of inflammatory cytokines, chemokines, and growth factors genes and is responsible for the immune and inflammatory response[29, 30]. It is thus suggested that NF-κB inhibition alleviates the inflammatory response, and various natural herbs and chemical agent affect anti-inflammatory response by inhibiting NF-κB signaling pathway[3133].…”
Section: Discussionmentioning
confidence: 99%